The Impact of Performative Language Teaching on Oral Skills in the Classroom of Chinese as a Foreign Language - Corderi Novoa, Modesto; García Mayo, María del Pilar (Sinología hispánica. China Studies Review, 2024)
This study examines the impact of Performative Language Teaching (PLT) techniques on speech variables such as fluency, comprehensibility, and accent. 16 learners of Mandarin Chinese (L1: Spanish) from the Official Language School in the city of Vigo in Spain were divided into an experimental group (8 students that in 2018 took part in a four-month PLT-based Chinese course) and a control group (8 students who did not participate in that course). Four different tasks (first-person picture description, third-person picture description, monologue, and improvised role-play dialogue) were used to obtain speech samples from the 16 learners. The two groups were tested before (pre-test) and after (post-test) participation. 75 native Chinese raters evaluated the recorded speech samples and the development of oral skills of both groups was compared. Our findings indicate that fluency, comprehensibility, and accent improved for the treatment group, but not for the comparison group. The improvement in fluency was greater than the improvement in comprehensibility and accent, which had similar degrees of development, although accent had slightly lower improvement scores than comprehensibility.